Active organic silicon modified acrylic emulsion as well as preparation method and application thereof
Through the application of active silicone-modified acrylic emulsion, the deficiencies in waterproofing and adhesion of existing concrete protective coatings are solved, the waterproofing, breathability and high adhesion of the coating are achieved, and the durability and service life of concrete are improved.
Patent Information
- Application Number
- CN202411536757.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-04-22
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-21
AI Technical Summary
The existing concrete protective coatings have shortcomings in waterproofness and adhesion, and are not breathable, which leads to the coating being easily damaged and failing during use.
The active organic silicon -modified acrylic lotion is adopted, and a co -reaction is performed by a co -reaction between the acrylic mono and the active sirusculus function monomer, which forms a hydrophobic, breathable, and high -adhesive water -based concrete anticorrosive coating.
The waterproofness, breathability and adhesion of concrete protective coatings are realized, the service life of the coating is extended, and the durability of concrete is improved.
Smart Images

Figure CN119331159A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete protection, and specifically relates to an active organosilicon-modified acrylic emulsion and a preparation method thereof, as well as application of the emulsion in concrete anticorrosive coatings. Background Art
[0002] Concrete is a porous material with a pore size distribution range of nanometers or even millimeters. Concrete deterioration is mainly determined by the rate at which water, air and other corrosive media penetrate into concrete. The main manifestations include freeze-thaw damage, salt crystallization, steel corrosion, alkali-aggregate reaction, sulfate, seawater and sewage erosion, etc. The harmful effects caused or generated by the water in the environment carrying harmful soluble substances into the concrete and the reversibility of the evaporable water in the concrete are important causes of concrete deterioration. In summary, for built concrete structures, the protective coating of concrete needs to meet the following three conditions: 1. Prevent water and harmful substances in the environment from entering the concrete, that is, the coating should increase the waterproofness of the concrete; 2. During the evaporation of water in the concrete, there is no damage to the coating, that is, the coating should be breathable; 3. The protective coating itself should be long-lasting, that is, it should have good adhesion, hardness and UV aging resistance.
[0003] There are two main types of concrete protective coatings commonly used at present. One is latex paint derived from architectural coatings. This type of coating has a large proportion of fillers and a small proportion of film-forming emulsions. Therefore, it has a certain degree of air permeability, but does not have waterproofness, sufficient hardness and adhesion. It often falls off and is damaged after one year of painting. The other is to use traditional industrial paint, that is, metal anti-corrosion paint, which is directly used for concrete protection. Generally, epoxy paint is used as the primer and intermediate layer, and polyurethane or fluorocarbon paint is used as the surface coating. This system has good initial hardness, adhesion, waterproofness and weather resistance, but it is not air permeable. After 2 to 3 years of use, it is damaged by the vapor pressure caused by the diffusion of water vapor inside the concrete, resulting in loss of adhesion, bulging, and coating damage, and protection failure.
[0004] In the coatings industry, water-based coatings use water to replace organic solvents. They are safe and non-toxic during production and use, and can meet the needs of energy conservation, emission reduction, recycling and sustainable development. The water-based nature of resins is an ideal way to reduce VOC emissions and is also the basis of water-based coatings. In order to ensure the smooth development of a green and low-carbon economy, the development of high-performance water-based emulsion coatings is a top priority for the coatings industry.
[0005] Water-based acrylic emulsions are mainly synthesized by emulsifying oily olefin monomers in water and initiating them with water-based free radical initiators. Acrylic emulsions are mainly used as base materials for latex paints and have an important application in the architectural coatings market. Currently, their applications are expanding, and their applications in the fields of industrial coatings and civil coatings are constantly expanding. However, there are still certain defects when they are directly used in the field of concrete anti-corrosion coatings.
[0006] Silicone polymers have the three characteristics of hydrophobicity, air permeability and super weather resistance. Therefore, it is considered to introduce active alkoxysilanes containing double bonds to improve hydrophobicity, air permeability and weather resistance by introducing silicon elements; and to improve the adhesion to the concrete interface by retaining active alkoxy groups. Conventional double-bond alkoxysilanes include vinyltriethoxysilane and γ-methacryloxypropyltrimethoxysilane, but there are usually certain problems. In addition to the double bonds involved in free radical emulsion polymerization, the monomer contains three alkoxy functional groups. First, the steric hindrance is large, resulting in low double bond reaction activity; second, there are more active alkoxy groups, and the possibility of hydrolysis and crosslinking during the emulsion polymerization process is also increased, resulting in the active alkoxy groups not being easy to preserve, and the system is prone to gelation reaction, resulting in a decrease in emulsion performance. The silicon-modified acrylate coating synthesized on this basis has no functional groups that can react with concrete, poor adhesion, and is easy to fall off.
[0007] The importance of concrete durability is self-evident. Therefore, there is an urgent need for a concrete protective coating that is waterproof and breathable, has good weather resistance, and has good adhesion to concrete to meet the demand for improving the durability of existing concrete. Summary of the invention
[0008] In view of the problems and shortcomings in the prior art, the present invention aims to provide a water-based concrete anti-corrosion coating and a preparation method thereof.
[0009] Based on the above purpose, the present invention adopts the following technical solution: In the first aspect, the present invention provides an active organosilicon-modified acrylic emulsion, wherein the weight composition of each 100 parts of the modified acrylic emulsion is: 35-55 parts of monomer, 0.1-5 parts of emulsifier, 0.01-0.2 parts of initiator, 0.1-0.5 parts of molecular weight regulator, 35-40 parts of buffer solution with a pH value of 7-7.5, and water is added to make up for the less than 100 parts; wherein the monomer is composed of an acrylate monomer A and an active silane functional monomer B, and the general formula of the active silane functional monomer B is , X is a carbon chain or ester chain containing a C=C double bond, R1 is a methyl group or an ethyl group, R is a methoxy group or an ethoxy group, and R' is the same as R1 or R; the amount of the active silane functional monomer B added accounts for 20% to 66.7% of the total amount of the monomers.
[0010] Preferably, the weight composition of the active silicone-modified acrylic emulsion is: 30 parts of acrylate monomer A, 20 parts of active silane functional monomer B, 2 parts of emulsifier, 0.15 parts of initiator, 0.2 parts of molecular weight regulator, 40 parts of buffer solution, and 7.65 parts of deionized water.
[0011] Preferably, the active silane functional monomer B is any one or more of vinyl diethoxymethyl silane (CAS No. 5507-44-8), vinyl ethoxy dimethyl silane (CAS No. 5356-83-2), γ-methacryloxypropyl diethoxymethyl silane (CAS No. 65100-04-1), and γ-methacryloxypropyl ethoxy dimethyl silane (CAS No. 13731-98-1).
[0012] Preferably, the acrylic ester monomer A is one or both of methyl acrylate and n-butyl acrylate.
[0013] Preferably, the buffer solution is prepared from a buffer system consisting of dihydrogen phosphate and dihydrogen salt of an alkali metal, or is prepared from tris(hydroxymethyl)aminomethane hydrochloride.
[0014] Preferably, the initiator is any one of dicyclohexyl percarbonate and di(2-ethylhexyl) percarbonate.
[0015] Preferably, the emulsifier is a mixture of Novelution 390 and Novelution KG2 in a mass ratio of (1:2) to (1:4).
[0016] Preferably, the molecular weight regulator is n-dodecyl mercaptan.
[0017] In a second aspect, the present invention provides a method for preparing a reactive silicone-modified acrylic emulsion, comprising the following steps: (1) adding an emulsifier to a buffer solution and stirring until the emulsifier is completely dissolved to obtain an emulsifier solution; (2) Mix the acrylic ester monomer A, the active silane functional monomer B, the molecular weight regulator, the initiator, and the remaining water uniformly, add them to the emulsifier solution obtained in step (1) under stirring, adjust the speed to 1500-2000 rpm, and perform pre-emulsification for 20 minutes; (3) After the pre-emulsification is completed, the speed is adjusted to 300-500 rpm, and the temperature is kept at 60±5℃ for 4-6 hours. After the reaction is completed, the temperature is lowered and filtered to obtain the active silicone-modified acrylic emulsion.
[0018] Preferably, the mixing time of adding to deionized water in step (1) is 2 to 5 minutes, and the rotation speed is 600 rpm.
[0019] Preferably, in step (1), after adding the emulsifier, stirring is performed for 10 to 20 minutes to obtain an emulsifier solution.
[0020] Preferably, the pre-emulsification in step (2) is performed until the liquid is allowed to stand for 3 minutes without stratification.
[0021] Preferably, the temperature in step (3) is lowered to 40°C.
[0022] Preferably, the filtration in step (3) uses an 80-mesh filter.
[0023] In a third aspect, the present invention provides the use of the active silicone-modified acrylic emulsion described in the first aspect in the preparation of an anti-corrosion coating.
[0024] In a fourth aspect, the present invention provides a water-based concrete anti-corrosion coating, which is composed of the following components, in parts by weight: 30 to 60 parts of the active silicone-modified acrylic emulsion described in the first aspect, 0 to 1 part of a thickener, 0.2 to 1 part of a wetting and dispersing agent, 0.1 to 0.5 parts of a bactericide, 0 to 40 parts of a filler, 0 to 25 parts of a pigment, 0 to 8 parts of a film-forming aid, and 10 to 30 parts of deionized water.
[0025] Preferably, the thickener is RM-8W.
[0026] Preferably, the wetting and dispersing agent is a mixture of SN5040 and PD405 in a mass ratio of 3:1.
[0027] Preferably, the bactericide is DB20.
[0028] Preferably, the filler is at least one of silicon dioxide and kaolin, wherein the particle size of silicon dioxide is 800 mesh and the particle size of kaolin is 1250 mesh.
[0029] Preferably, the pigment is titanium dioxide.
[0030] Preferably, the film-forming aid is alcohol ester dodecahydrate.
[0031] In a fifth aspect, the present invention provides a method for preparing a water-based concrete anticorrosive coating, comprising the following steps: S1. Add the wetting dispersant and fungicide into deionized water, disperse at 500-700 rpm for 10-15 minutes, then add the pigment and filler, adjust the speed to 1000-1500 rpm and disperse for 40-50 minutes; S2. After dispersion, adjust the speed to 700-1000rpm, add active silicone modified acrylic emulsion in sequence, disperse for 5-8min, add film-forming aid, disperse for 10-15min, add thickener, adjust KU value to 70-90, disperse for 20-30min, filter, and obtain water-based concrete anticorrosive coating.
[0032] Preferably, the dispersion process uses a high-speed disperser.
[0033] Preferably, the filtration in S2 uses an 80-mesh filter.
[0034] The active silane functional monomer B used in the present invention can be purchased from a commercial product, or can be prepared by alcoholysis of the corresponding chlorosilane. Vinyl diethoxymethyl silane and γ-methacryloxypropyl diethoxymethyl silane can be selected from vinyl methyl dichlorosilane and γ-methacryloxypropyl methyl dichlorosilane as reaction raw materials, respectively. The reaction route is: ; Vinylethoxydimethylsilane and γ-methacryloxypropylethoxydimethylsilane are selected from vinyldimethyl monochlorosilane and γ-methacryloxypropyl dimethyl monochlorosilane as reaction raw materials, respectively, and the reaction route is: , In the above reaction scheme, X is .
[0035] The specific preparation process is: A. Add chlorosilane (vinylmethyldichlorosilane, vinyldimethylmonochlorosilane, γ-methacryloxypropylmethyldichlorosilane or γ-methacryloxypropyldimethylmonochlorosilane) to a flask equipped with a condenser, add ethanol under stirring, raise the temperature to 60°C, and reflux for 60 minutes to obtain a crude product; B. Add triethylamine to the crude product to neutralize the hydrogen chloride in the crude product, then distill at atmospheric pressure, and remove the remaining ethanol from the reaction at 78-80°C; C. Perform vacuum distillation on the remaining material at a pressure of 2.0 KPa and a temperature of 60°C. Collect the colorless transparent liquid in the distillate, which is the product.
[0036] Compared with the prior art, the present invention has the following beneficial effects: 1. In the present invention, when selecting the type of active alkoxy group, the alkoxy group is selected from methoxy group and ethoxy group. Compared with methoxy group, ethoxy group has smaller polarity, larger substituent and stronger stability. Therefore, active silane monomer containing ethoxy group is preferably used for copolymerization with acrylate monomer. Hydrolysis and crosslinking are less likely to occur during emulsion polymerization, and more active alkoxy groups can be retained.
[0037] 2. Considering the greater electron-donating effect of ethoxy, the lower the ethoxy content in the molecular structure, the more stable a single ethoxy group is. The present invention selects an active silane functional monomer with one or two ethoxy groups. Compared with an active silane functional monomer with three ethoxy groups, the former is less likely to hydrolyze and crosslink in emulsion polymerization, so that more silane monomers can be added to the system, which is beneficial to increase the content of organic silicon in the system and further improve the distribution uniformity of ethoxy groups in concrete anticorrosive coatings.
[0038] 3. In the process of emulsion polymerization, the buffer solution is used to adjust the pH value of the system to between 7.0 and 7.5, and the initiator is used to allow the emulsion polymerization to be carried out at a relatively low temperature. The neutral and relatively low reaction temperature can stabilize the active siloxane groups in the silane, and prevent the occurrence of cross-linking reactions during the reaction process, thereby increasing the amount of the added active silane functional monomer B containing double bonds, ensuring that the double bonds in the active silane functional monomer B and the double bonds in the acrylate monomer A can smoothly undergo free radical emulsion copolymerization, retaining as many active ethoxy functional groups as possible, and reducing the gelation phenomenon caused by the hydrolysis of active ethoxy groups.
[0039] 4. The active organosilicon modified acrylic emulsion prepared by the present invention is a complex mixed substance, and the reaction mechanism is mainly based on the free radical emulsion polymerization of double bonds. A small part of the ethoxy groups in the side chain undergoes hydrolysis and crosslinking, which acts as a crosslinking monomer in the emulsion polymerization and plays a role in chain extension, and most of it remains on the side chain in the form of ethoxy groups. The formed emulsion structure still has a carbon chain as the main chain, and the side chain contains active ethoxy groups.
[0040] 5. The present invention prepares concrete anticorrosive coatings based on active organosilicon-modified acrylic emulsions without adding amine additives, so that the coating environment remains in a neutral state, thereby ensuring the stability of active ethoxy groups and further ensuring the storage stability of the coating; the pH value of concrete is usually between 8 and 14, showing strong alkalinity. When the concrete anticorrosive coating is applied to the concrete, the alkalinity of the concrete can catalyze the hydrolysis of active alkoxy groups, which form silanol groups after hydrolysis. A part of them undergoes chemical reactions with the concrete substrate to form stable chemical bonds, and the other part is used for self-crosslinking of the system, thereby increasing the crosslinking degree of the coating itself and thereby increasing the hardness and adhesion of the coating. The reaction mechanism is as follows: S1. Under the catalysis of concrete alkalinity, the active alkoxy groups retained in the chain segments are hydrolyzed to form silanol groups; S2. A portion of the silanol groups cross-link between the molecular chains to form a -Si-O-Si- structure, further increasing the degree of cross-linking; S3. A portion of the silanol groups react with concrete to form covalent bonds and bond with the concrete.
[0041] It should be noted that S2 and S3 are carried out simultaneously, in no particular order.
[0042] That is to say, under the catalytic action of the alkalinity of concrete, the ethoxy groups in the side chains are hydrolyzed to form silanol groups; further, a part of the silanol groups self-crosslink to increase the crosslinking degree and hardness of the coating; a part of the silanol groups react with the hydroxyl groups in the concrete to form chemical bonds with the concrete substrate, thereby improving the bonding strength between the coating and the substrate.
[0043] 6. The concrete anticorrosive coating prepared by the present invention improves the air permeability of the system by introducing silicon elements, and improves the cross-linking degree of the system and the bonding strength with concrete by introducing silanol groups, and has a good protective effect. It can reduce the penetration of harmful substances carried by water in the environment into the concrete, and does not affect the escape of water vapor inside the concrete, so that the durability of the coating and concrete is improved, meeting the requirements of anti-corrosion under severe weather and freeze-thaw damage, improving overall safety, extending service life, reducing replacement cycles, and saving energy and reducing emissions. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 This is a comparison diagram of the adhesion of sample 1-2-1 in Example 1 before and after the test; Figure 2 It is a line graph of the mass loss after drying for 8 hours for samples 1-2-1, 1-2-2 and comparative sample 1-2-1 in Example 1; Figure 3 This is a bar graph of the mass loss of samples 1-2-1, 1-2-2 and comparative sample 1-2-1 in Example 1 after drying for 8 hours. DETAILED DESCRIPTION
[0045] The following examples are only for further explanation of the present invention. It should be noted that all technical and scientific terms used in the present invention have the same meanings as in the technical field to which the present invention belongs unless otherwise specified. The experimental methods in the following examples without specifying specific conditions are all based on conventional techniques in the technical field, or according to the conditions recommended by the manufacturer; the reagents or instruments used without specifying the manufacturer are all conventional products that can be purchased commercially.
[0046] In order to make the purpose, technical solution and advantages of the present invention clearer and more specific, the present invention is further described in detail by examples below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0047] Example 1 Effect of the Type of Monomer B on Waterborne Concrete Anticorrosive Coating 1. Preparation of reactive silicone modified acrylic emulsion Prepare the materials with reference to the raw materials and dosage requirements in Table 1, and prepare the active silicone-modified acrylic emulsion by the following method to obtain samples 1-1-1 and 1-1-2, and comparative samples 1-1-1 and 1-1-2: (1) Place a condenser reflux tube and a thermometer in a four-necked flask, add a buffer (according to the quantitative standard in Table 1, the comparative sample 1-1-1 does not contain a buffer, but is replaced by 40 parts of deionized water), mix at 600 rpm for 5 minutes until the pH value is 7.4, then add an emulsifier from the feed port and stir for 10 minutes until the emulsifier is completely dissolved to obtain an emulsifier solution; (2) The acrylic ester monomer A, the active silane functional monomer B, the molecular weight regulator and the initiator are uniformly mixed and added to the emulsifier solution obtained in step (1) under stirring. The speed is adjusted to 1500 rpm and pre-emulsification is performed for 20 minutes. At this time, the liquid is allowed to stand for 3 minutes without stratification; (3) After the pre-emulsification is completed, the speed is adjusted to 400 rpm, and the temperature is kept at 60°C for 6 hours. After the reaction is completed, the temperature is lowered to 40°C and filtered through an 80-mesh filter to obtain an active silicone-modified acrylic emulsion.
[0048] Table 1 Raw material composition of samples 1-1-1 to 1-1-2 and comparative samples 1-1-1 to 1-1-2 After the preparation of samples 1-1-1 to 1-1-2 and comparison samples 1-1-1 to 1-1-2 was completed, the mass of the residue on the filter was weighed, and the residue was weighed after drying, and the (dry weight of the residue / theoretical solid content)*100% was calculated to obtain the gel rate, and the pH value and average particle size of the obtained silicone-modified acrylic emulsion were measured. The measurement results are shown in Table 2.
[0049] Table 2 Performance of samples 1-1-1 to 1-1-2 and comparative samples 1-1-1 to 1-1-2 As can be seen from Table 2, since the vinyl triethoxysilane in the comparative sample 1-1-2 contains four functional groups, in addition to the vinyl group that participates in free radical polymerization, it also has three ethoxy groups that can be cross-linked. When the addition amount is 30% of the total monomer content, even if the reaction temperature and the pH value of the system are controlled, gelation reaction still occurs and it is unusable. The remaining three, namely comparative sample 1-1-1, sample 1-1-1 and sample 1-1-2, are usable active silicone modified acrylic emulsions.
[0050] Preparation of water-based concrete anticorrosive coating The emulsion samples 1-1-1 and 1-2-1 prepared in step 1 are used as main raw materials, and the raw materials are prepared with reference to the raw materials and dosage requirements in Table 3. Further, water-based concrete anticorrosive coatings are prepared by the following method to obtain samples 1-2-1 and 1-2-2: S1. In the material tank of the high-speed disperser, add deionized water, wetting dispersant and fungicide, disperse at 500rpm for 10min, then add pigment and filler, adjust the speed to 1000rpm and disperse for 40min; S2. After dispersion, adjust the speed to 800rpm, add active silicone modified acrylic emulsion in sequence, disperse for 5min, add film-forming aid, disperse for 10min, add thickener, adjust KU value to 70-90, disperse for 20min, filter, and obtain water-based concrete anticorrosive coating.
[0051] Comparative sample 1-2-1 was prepared based on the same method, and the amount of alcohol ester dodecahydrate added in comparative sample 1-2-1 was 0.
[0052] Table 3 Raw material composition of samples 1-2-1 to 1-2-2 and comparative sample 1-2-1 The above-mentioned sample 1-2-1, sample 1-2-2 and comparative sample 1-2-1 were respectively coated on concrete test blocks. After curing at room temperature for 7 days, the pencil hardness of the paint film, the adhesion to the concrete substrate, the water absorption rate of the test block after coating, and the weather resistance were tested. The results are shown in Table 4.
[0053] Table 4 Performance of samples 1-2-1 to 1-2-2 and comparative sample 1-2-1 Figure 1 The comparison chart of sample 1-2-1 before and after the adhesion test is shown. The test method is: take 6 concrete test blocks of 70*70*40mm in each group, polish and then paint the prepared samples. After curing for 7 days, use adhesive to bond the mold and the painted surface together. Use a universal testing machine to quantitatively test the adhesion by pulling apart. Among the two test pieces on the left, one part is the bonding failure between the adhesive and the mold, one part is the adhesion failure between the coating and the substrate, and one part is the cohesive failure of the substrate. For the four test pieces on the right, one part is the adhesion failure between the coating and the substrate, and one part is the cohesive failure of the substrate. It meets the standard test requirements, which indirectly shows that the adhesion between the coating and the substrate is equivalent to the cohesive force between the coating, the adhesive and the substrate.
[0054] Take three groups of 100×100mm×100mm concrete test blocks, three in each group, and seal five of their faces with sample 1-2-1, sample 1-2-2, and comparison sample 1-2-1, respectively. After curing for 7 days, soak the concrete test blocks in water for 48 hours to make them saturated with water. Take them out and place them for 2 hours until there is no visible water on the surface. Then apply two coats of the above samples 1-2-1 to 1-2-2 and comparison sample 1-2-1 (controlled at 300±50g / m 2 ), after curing for 7 days, place it in an oven at 60℃ and blow dry it. The mass loss, that is, the mass of moisture dried out, is measured once an hour to characterize the air permeability. The more the mass of moisture dried out, the better the air permeability. The results are as follows: Figures 2-3 shown.
[0055] From Table 4, Figures 1 to 3 It can be seen that compared with the comparative sample 1-1-1, the samples 1-1-1 and 1-1-2 prepared in Example 1 can significantly improve the hardness of the paint film of the concrete anticorrosive coating, the adhesion between the paint film and the concrete test block, and reduce the water absorption rate of the test block due to the introduction of active organic silicon. After coating, the air permeability of samples 1-2-1 and 1-2-2 is also significantly higher than that of the comparative sample 1-2-1. Therefore, the samples 1-1-1 and 1-1-2 prepared in Example 1 meet the use requirements of the concrete anticorrosive coating and have high application value.
[0056] Example 2 Effect of the amount of monomer B (vinyl diethoxymethyl silane) added on water-based concrete anticorrosive coating 1. Preparation of reactive silicone modified acrylic emulsion The amount of vinyl diethoxymethyl silane monomer was adjusted to prepare different samples of active silicone-modified acrylic emulsions by the following method. The sample numbers and corresponding raw material amounts are shown in Table 5: (1) Place a condenser reflux tube and a thermometer in a four-necked flask, add deionized water and a buffer, mix at 600 rpm for 5 min until the pH value reaches 7.3, then add an emulsifier from the feed port and stir for 10 min until the emulsifier is completely dissolved to obtain an emulsifier solution; (2) The acrylic ester monomer A, the active silane functional monomer B, the molecular weight regulator and the initiator are mixed evenly, and added to the emulsifier solution obtained in step (1) under stirring, and the rotation speed is adjusted to 1600 rpm, and pre-emulsification is performed for 20 minutes until the liquid is allowed to stand for 3 minutes without stratification; (3) After the pre-emulsification is completed, the speed is adjusted to 300 rpm, and the temperature is kept at 60°C for 6 hours. After the reaction is completed, the temperature is lowered to 40°C and filtered through an 80-mesh filter to obtain an active silicone-modified acrylic emulsion.
[0057] Table 5 Raw material composition of modified acrylic emulsion samples 2-1-1 to 2-1-5 The prepared modified acrylic emulsion samples were observed and found that with the increase of the amount of monomer B added, especially when the amount of monomer B added accounted for more than 40% of the total monomer, the system showed gelation during the emulsification reaction, which resulted in only sample 2-1-1, sample 2-1-2 and sample 2-1-3 being usable emulsions among the above five samples. This may be because when vinyl diethoxymethyl silane was selected as the active silane functional monomer B, it contained two active ethoxy groups and had strong activity; when its addition accounted for a high proportion of the monomer, excessive ethoxy groups were hydrolyzed to form silanol groups, which further self-crosslinked to form gel. Therefore, it is necessary to control the amount of monomer B added.
[0058] Preparation of water-based concrete anticorrosive coating Take samples 2-1-1, 2-1-2, and 2-1-3, and refer to the raw material dosage and preparation method of concrete anti-corrosion coating sample 1-2-1 to prepare corresponding concrete anti-corrosion coating samples 2-2-1, 2-2-2, and 2-2-3 respectively.
[0059] Concrete anticorrosion coating samples 2-2-1, 2-2-2 and 2-2-3 were coated on concrete test blocks respectively. After curing at room temperature for 7 days, the adhesion between the paint film and the concrete substrate and the water absorption rate of the test blocks after coating were tested. The results are shown in Table 6.
[0060] Table 6 Performance of samples 2-2-1 to 2-2-3 and comparative sample 1-2-1 It can be seen from Table 6 that the performance of concrete anticorrosive coating samples 2-2-1, 2-2-2, and 2-2-3 prepared in Example 2 is better than that of comparative sample 1-2-1. In addition, as the content of vinyl diethoxymethyl silane in the active organosilicon-modified acrylic emulsion increases, the silicon content and the content of active functional groups increase accordingly, so the adhesion of the prepared coating increases and the water absorption rate decreases.
[0061] Example 3 Effect of the amount of monomer B (vinylethoxydimethylsilane) added on water-based concrete anticorrosive coating 1. Preparation of reactive silicone modified acrylic emulsion Different amounts of vinylethoxydimethylsilane were added to prepare different reactive silicone-modified acrylic emulsion samples by the following method. The sample numbers and corresponding raw material amounts are shown in Table 7: (1) Place a condenser reflux tube and a thermometer in a four-necked flask, add deionized water and a buffer, mix at 600 rpm for 5 min until the pH value reaches 7.2, then add an emulsifier from the feed port and stir for 10 min until the emulsifier is completely dissolved to obtain an emulsifier solution; (2) The acrylic ester monomer A, the active silane functional monomer B, the molecular weight regulator and the initiator are uniformly mixed and added to the emulsifier solution obtained in step (1) under stirring. The rotation speed is adjusted to 1700 rpm and pre-emulsification is performed for 20 minutes until the liquid is allowed to stand for 3 minutes without stratification; (3) After the pre-emulsification is completed, the speed is adjusted to 400 rpm, and the temperature is kept at 60°C for reaction for 5 hours. After the reaction is completed, the temperature is lowered to 40°C and filtered through an 80-mesh filter to obtain an active silicone-modified acrylic emulsion.
[0062] Table 7 Raw material composition of modified acrylic emulsion samples 3-1-1 to 3-1-5 The obtained modified acrylic emulsion samples 3-1-1 to 3-1-5 were observed, and it was found that sample 3-1-5 gelled during the emulsification reaction, and the product was unusable, while the other four samples, namely samples 3-1-1 to 3-1-4, were usable. Compared with vinyl diethoxymethylsilane, vinyl ethoxy dimethyl silane has only one ethoxy group, and is less likely to gel than the former, but the addition amount still needs to be controlled, and the addition amount in the total monomer should not exceed 55.6%.
[0063] Preparation of water-based concrete anticorrosive coating Take modified acrylic emulsion samples 3-1-1 to 3-1-4, and refer to the raw material dosage and preparation method of concrete anti-corrosion coating sample 1-2-1 to prepare corresponding concrete anti-corrosion coating samples 3-2-1, 3-2-2, 3-2-3, and 3-2-4 respectively. The specific composition of the raw materials is shown in Table 8.
[0064] Table 8 Raw material composition of concrete anticorrosive coating samples 3-2-1 to 3-2-4 Take concrete anticorrosive coating samples 3-2-1 to 3-2-4, apply them on concrete test blocks respectively, and after curing at room temperature for 7 days, test the adhesion between the paint film and the concrete substrate and the water absorption rate of the test blocks after coating. The results are shown in Table 9.
[0065] Table 9 Performance of samples 3-2-1 to 3-2-4 and comparative sample 1-2-1 As can be seen from Table 9, the performance of samples 3-2-1 to 3-2-4 prepared in Example 3 is better than that of comparative sample 1-2-1. At the beginning, as the content of vinylethoxydimethylsilane in the emulsion increases, the silicon content and the content of active functional groups increase accordingly, the adhesion of the prepared coating increases, the water absorption rate decreases, and the performance is optimal when the proportion of vinylethoxydimethylsilane added in the total monomer reaches 40%; continue to increase the proportion of silane, when the proportion of vinylethoxydimethylsilane added in the total monomer reaches 50%, the adhesion of the corresponding anti-corrosion coating decreases, and the water absorption rate increases. This may be because when the silicon content is too large, more silanol groups are formed after the hydrolysis of ethoxy groups, and the silanol groups are self-crosslinked before they have time to react with concrete, thereby affecting the adhesion on the concrete surface and increasing the water absorption rate.
[0066] Example 4 Effect of the Addition Amount of Monomer B (γ-Methacryloxypropylethoxydimethylsilane) on Waterborne Concrete Anticorrosive Coating 1. Preparation of reactive silicone modified acrylic emulsion Different amounts of γ-methacryloxypropylethoxydimethylsilane were added to prepare different reactive silicone-modified acrylic emulsion samples by the following method. The sample numbers and corresponding raw material amounts are shown in Table 10: (1) Place a condenser reflux tube and a thermometer in a four-necked flask, add deionized water and a buffer, mix at 600 rpm for 5 min until the pH value reaches 7.1, then add an emulsifier from the feed port and stir for 10 min until the emulsifier is completely dissolved to obtain an emulsifier solution; (2) The acrylic ester monomer A, the active silane functional monomer B, the molecular weight regulator and the initiator are uniformly mixed and added to the emulsifier solution obtained in step (1) under stirring. The rotation speed is adjusted to 1800 rpm and pre-emulsification is performed for 20 minutes until the liquid is allowed to stand for 3 minutes without stratification; (3) After the pre-emulsification is completed, the speed is adjusted to 500 rpm, and the temperature is kept at 60°C for 4 hours. After the reaction is completed, the temperature is lowered to 40°C and filtered through an 80-mesh filter to obtain an active silicone-modified acrylic emulsion.
[0067] Table 10 Raw material composition of samples 4-1-1 to 4-1-5 After the preparation of samples 4-1-1 to 4-1-5 is completed, the five ratios are all usable active silicone-modified acrylic emulsions.
[0068] Preparation of water-based concrete anticorrosive coating Take modified acrylic emulsion samples 4-1-1 to 4-1-5, and refer to the raw material dosage and preparation method of concrete anti-corrosion coating sample 1-2-1 to prepare corresponding concrete anti-corrosion coating samples 4-2-1, 4-2-2, 4-2-3, and 4-2-4 respectively. The specific composition of the raw materials is shown in Table 11.
[0069] Table 11 Raw material composition of concrete anticorrosive coating samples 4-2-1 to 4-2-5 Take concrete anticorrosive coating samples 4-2-1 to 4-2-5, apply them on concrete test blocks respectively, and after curing at room temperature for 7 days, test the adhesion of the paint film to the concrete substrate and the water absorption rate of the test blocks after coating. The results are shown in Table 12.
[0070] Table 12 Performance of samples 4-2-1 to 4-2-5 and comparative sample 1-2-1 It can be seen from Table 12 that the performance of samples 4-2-1 to 4-2-5 prepared in Example 4 is better than that of comparative sample 1-2-1.
[0071] As the content of γ-methacryloxypropylethoxydimethylsilane in the emulsion increases, the silicon content and the content of active functional groups increase, and the adhesion of the prepared coating first gradually increases, and then shows a downward trend after reaching a peak, which is similar to the situation in Example 3; while the water absorption rate first decreases, and then gradually increases after the content of silane in the monomer reaches 55.6%.
[0072] The present invention effectively overcomes the deficiencies in the prior art and has a high industrial utilization value. The above embodiments are used to illustrate the substantive content of the present invention, but are not intended to limit the protection scope of the present invention. It should be understood by those skilled in the art that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and protection scope of the technical solution of the present invention.
Claims
1. An active silicone-modified acrylic emulsion, characterized in that: The weight composition of each 100 parts of the modified acrylic emulsion is: 35-55 parts of monomer, 0.1-5 parts of emulsifier, 0.01-0.2 parts of initiator, 0.1-0.5 parts of molecular weight regulator, 35-40 parts of buffer solution with a pH value of 7-7.5, and water is added to make up for the less than 100 parts; wherein the monomer is composed of an acrylic ester monomer A and an active silane functional monomer B, and the general formula of the active silane functional monomer B is , X is a carbon chain or ester chain containing a C=C double bond, R1 is a methyl group or an ethyl group, R is a methoxy group or an ethoxy group, and R' is the same as R1 or R; the amount of the active silane functional monomer B added accounts for 20% to 66.7% of the total amount of the monomers.
2. The reactive silicone-modified acrylic emulsion according to claim 1, characterized in that: The active silane functional monomer B is one or more of vinyl diethoxymethyl silane, vinyl ethoxy dimethyl silane, γ-methacryloxypropyl diethoxymethyl silane, and γ-methacryloxypropyl ethoxy dimethyl silane.
3. The reactive silicone-modified acrylic emulsion according to claim 2, characterized in that: The acrylic acid ester monomer A is one or both of methyl acrylate and n-butyl acrylate.
4. The reactive silicone-modified acrylic emulsion according to claim 3, characterized in that: The buffer solution is prepared from a buffer system consisting of dihydrogen phosphate and dihydrogen salt of alkali metals, or is prepared from tris(hydroxymethyl)aminomethane hydrochloride.
5. The reactive silicone-modified acrylic emulsion according to claim 4, characterized in that: The initiator is any one of dicyclohexyl percarbonate and di(2-ethylhexyl) percarbonate.
6. The reactive organosilicon-modified acrylic emulsion according to claim 5, characterized in that: The emulsifier is a mixture of Novelution 390 and Novelution KG2 in a mass ratio of (1:2) to (1:4).
7. The method for preparing the reactive silicone-modified acrylic emulsion according to claim 1, characterized in that: The following steps are involved: (1) adding an emulsifier to a buffer solution and stirring until the emulsifier is completely dissolved to obtain an emulsifier solution; (2) Evenly mix the measured amount of acrylic ester monomer A, active silane functional monomer B, molecular weight regulator, initiator, and the remaining amount of water, add them to the emulsifier solution obtained in step (1) under stirring, adjust the speed to 1500-2000 rpm, and perform pre-emulsification for 20 minutes; (3) After the pre-emulsification is completed, the speed is adjusted to 300-500 rpm, and the temperature is kept at 60±5℃ for 4-6 hours. After the reaction is completed, the temperature is lowered and filtered to obtain the active silicone-modified acrylic emulsion.
8. Use of the reactive organosilicon-modified acrylic emulsion according to any one of claims 1 to 7 in the preparation of anticorrosive coatings.
9. A water-based concrete anticorrosive coating, characterized in that: The invention is composed of the following components in parts by weight: 30-60 parts of the active organosilicon-modified acrylic emulsion according to claim 1, 0-1 part of a thickener, 0.2-1 part of a wetting and dispersing agent, 0.1-0.5 part of a bactericide, 0-40 parts of a filler, 0-25 parts of a pigment, 0-8 parts of a film-forming aid, and 10-30 parts of deionized water.
10. The method for preparing the water-based concrete anticorrosive coating according to claim 9, characterized in that: The following steps are involved: S1. Add the wetting dispersant and fungicide into deionized water, disperse at 500-700 rpm for 10-15 minutes, then add the pigment and filler, adjust the speed to 1000-1500 rpm and disperse for 40-50 minutes; S2. After dispersion, adjust the speed to 700-1000rpm, add active silicone modified acrylic emulsion in sequence, disperse for 5-8min, add film-forming aid, disperse for 10-15min, add thickener, adjust KU value to 70-90, disperse for 20-30min, filter, and obtain water-based concrete anticorrosive coating.